A comparative study of conditioning programs in relation to performance of Malaysian endurance horses - Mohd Zulkaffli, Hazira Filza; Mohd Adzahan, Noraniza; Omar, Mohamed Ariff (2012)
Conditioning provides physiological adaptation, resulting increase in fitness of athletics horses, which eventually increase their performance. The primary aim of a conditioning program is to produce the best performing athletic horse with minimal injuries. A survey was conducted using a questionnaire to identify various conditioning programs practiced by the local endurance horse establishments with regards to techniques and duration of the program. Fifteen athletic endurance horses with three horses each representing five equine establishments were used in this study. The duration of every conditioning program were recorded. Performance parameters that were monitored were the average recovery time, the average speed, the completion rate and the level of performance. Kruskal-Wallis test was used to compare conditioning programs practiced by different establishments in relation to their performances. The mean of the average speed of horses from different establishments ranged from 9.30 to 15.20 km hr-1. Stable A that practices all basic endurance conditioning techniques with a duration period of conditioning of >3 months showed the highest speed (15.20 ± 0.05 km hr-1) and the shortest mean of the average recovery period (12.28± 1.18 min) with a 100 % completion rate in 120 km endurance race category. Therefore, the conditioning program practiced by Stable A is suggested to be an optimal conditioning program suited for horses under Malaysian conditions in producing good and competitive endurance horses locally.